2014
DOI: 10.1126/science.1248465
|View full text |Cite
|
Sign up to set email alerts
|

A Viral RNA Structural Element Alters Host Recognition of Nonself RNA

Abstract: Although interferon (IFN) signaling induces genes that limit viral infection, many pathogenic viruses overcome this host response. As an example, 2′-O methylation of the 5′ cap of viral RNA subverts mammalian antiviral responses by evading restriction of Ifit1, an IFN-stimulated gene that regulates protein synthesis. However, alphaviruses replicate efficiently in cells expressing Ifit1 even though their genomic RNA has a 5′ cap lacking 2′-O methylation. We show that pathogenic alphaviruses use secondary struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
188
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(200 citation statements)
references
References 46 publications
9
188
3
Order By: Relevance
“…To extend these findings to another family of RNA viruses that cause CNS disease, we evaluated the pathogenesis of VEEV, an encephalitic alphavirus, in Asyn-knockout mice. We used an attenuated strain of VEEV (TC83) that cannot escape IFIT1 restriction (33). Using VEEV TC83, we found that the virus grew to titers of up to 10 8 PFU per gram of brain tissue in the brains of Asyn-knockout mice, and Asyn-knockout mice experienced significant disease from VEEV TC83, as evidenced by increased weight loss compared to that found in TC83-inoculated Snca Ϫ/ϩ mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To extend these findings to another family of RNA viruses that cause CNS disease, we evaluated the pathogenesis of VEEV, an encephalitic alphavirus, in Asyn-knockout mice. We used an attenuated strain of VEEV (TC83) that cannot escape IFIT1 restriction (33). Using VEEV TC83, we found that the virus grew to titers of up to 10 8 PFU per gram of brain tissue in the brains of Asyn-knockout mice, and Asyn-knockout mice experienced significant disease from VEEV TC83, as evidenced by increased weight loss compared to that found in TC83-inoculated Snca Ϫ/ϩ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Using a neuroinvasive WNV strain, we found that Asyn expression inhibited the growth of infectious viral particles in the brain. We next used a vaccine strain of an alphavirus, Venezuelan equine encephalitis virus (VEEV; strain TC83), to determine if Asyn expression inhibits the growth of virus from a different enveloped RNA virus family not related to WNV (33 ) from TC83-infected Snca Ϫ/Ϫ mice was significantly (P ϭ 0.03, ANOVA with the Mann-Whitney test) increased compared with that in striatal and cortical tissue from Snca Ϫ/ϩ mice, in which virus was undetectable (Fig. 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Type I interferon secretion leads to the transcription of hundreds of interferon-stimulated genes, which display antiviral properties by targeting almost any step of the virus replication cycle (66). Interestingly, Hyde and colleagues demonstrated that alphaviruses, which are also single-stranded, positive-strand RNA viruses, use mutations within the 5= noncoding region affecting secondary-structural elements of their RNAs to alter interferon-stimulated protein binding and functions (67). Their results suggest an evasion mechanism by which a deleted virus with modified 5= RNA secondary structures could avoid immune restriction, despite type 1 IFN secretion and interferon-stimulated gene transcription, leading to long-term virus persistence in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Chimeric flaviviruses have been engineered to study pathogenesis (Yoshii et al, 2014), replication regulation and virushost interaction (Courtney et al, 2012;Evans & Seeger, 2007;Hyde et al, 2014). Especially, using live attenuated strains as the genetic backbone, multiple versions of chimeric flaviviruses have been successfully designed and well-explored in the development of vaccines against DENV, WNV, JEV and TBEV (Brandler et al, 2005;Chambers et al, 1999;Guirakhoo et al, 2000;Guy & Jackson, 2016;Pletnev et al, 2002;Wright et al, 2008).…”
mentioning
confidence: 99%